2004
DOI: 10.1038/sj.onc.1207886
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gene-expression profiles between diffuse- and intestinal-type gastric cancers using a genome-wide cDNA microarray

Abstract: Gastric cancer is the fourth leading cause of cancerrelated death in the world. Two histologically distinct types of gastric carcinoma, 'intestinal' and 'diffuse', have different epidemiological and pathophysiological features that suggest different mechanisms of carcinogenesis. A number of studies have investigated intestinal-type gastric cancers at the molecular level, but little is known about mechanisms involved in the diffuse type, which has a more invasive phenotype and poorer prognosis. To clarify the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
1
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 29 publications
(20 reference statements)
7
84
1
1
Order By: Relevance
“…Thus, in concordance with other studies, this work demonstrates that a gene expression profile-based stratification of these histological types of gastric adenocarcinoma is possible and useful, and that phenotypic differences are reflections of broad molecular distinctiveness. [10][11][12][13]36 However, this study is the first to analyze gene expression on a transcriptome-wide level, thus, providing the most comprehensive view of gene expression profiles possible to date. This also explains why the study revealed a higher number of differentially expressed genes than had been found in previous work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, in concordance with other studies, this work demonstrates that a gene expression profile-based stratification of these histological types of gastric adenocarcinoma is possible and useful, and that phenotypic differences are reflections of broad molecular distinctiveness. [10][11][12][13]36 However, this study is the first to analyze gene expression on a transcriptome-wide level, thus, providing the most comprehensive view of gene expression profiles possible to date. This also explains why the study revealed a higher number of differentially expressed genes than had been found in previous work.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are fully consistent with previous studies. 10,11 However, this work is the first to use a statistical approach to underline the strong differences in biology and gene functions between these two types of adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After amplified RNAs (aRNAs) were labeled with Cy3 or Cy5, respectively, we carried out hybridization between labeled aRNAs and cDNA microarray slides containing 36 864 spots and detected the signals. Expression of CDC20 in various cancer tissues and their corresponding normal tissues were examined by using data sets that were analysed previously (Ono et al, 2000;Kitahara et al, 2001;Okabe et al, 2001;Hasegawa et al, 2002;Kaneta et al, 2002;Kitahara et al, 2002;Nagayama et al, 2002;Okutsu et al, 2002;Kikuchi et al, 2003;Okada et al, 2003;Ashida et al, 2004;Jinawath et al, 2004;Nakamura et al, 2004;Nishidate et al, 2004;Ochi et al, 2004;Obama et al, 2005;Takata et al, 2005;Hirota et al, 2006;Taniwaki et al, 2006;Yamabuki et al, 2006). To select genes that were suppressed by p53 and upregulated in various cancer tissues, the following two criteria were used: (1) genes whose expression were more than threefold decreased by Ad-p53 and (2) genes whose expression were more than threefold increased in various cancer tissues compared with its corresponding normal tissues.…”
Section: Cdna Microarraysmentioning
confidence: 99%
“…However, available studies have primarily dealt with comparisons of normal tissues, or precancerous lesions, with advanced tumors (Boussioutas et al, 2003;Meireles et al, 2004;Yu et al, 2005) or with the determination of profiles associated with the most common histotypes, intestinal and diffuse ( Hippo et al, 2001;Hasegawa et al, 2002;Kim et al, 2003;Jinawath et al, 2004;Norsett et al, 2004). Much less is known in terms of comparison between EGC and AGC, owing to the limited number of samples analysed and owing to the difficulty of evaluating the impact of non-cancerous cells within the tumor tissue Oue et al, 2004).…”
Section: Introductionmentioning
confidence: 99%